EVALUASI PELATIHAN KEPEMIMPINAN PENGAWAS SECARA E-LEARNING DI BPSDM PEMERINTAH PROVINSI DKI JAKARTA - Abdul Kholik (LP3M Universitas Muhammadiyah Muara Bungo, 2021)
This study aims to determine the effectiveness of the implementation of Supervisory Leadership Training at BPSDM DKI Jakarta Provincial Government in the process and outcome aspects. This type of research is descriptive research. Descriptive research describes the characteristics of the aspects of the phenomenon or population being studied. The research method used is a qualitative approach. Data collection techniques through interviews, questionnaires and documentation studies. Research instruments in the form of interview guidelines, questionnaires and document guidelines. The evaluation used is the CIPP model which consists of Context, Input, Process and Product. However, in this study there are only two aspects, namely Process and Product. The results showed that all components in the implementation process were carried out effectively. And the product or result aspect, all participants passed 100% with average ability with the predicate